Teoretyczne uwarunkowania procesu modernizacji gospodarstw rolniczych - Wasilewska, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
Considering the common use of the term “modernization” in socio-economic policy and the lack of common definition of this term, the author makes broad literature review. The research objective of the paper is to specify theoretical features of modernization, which should be the background for policy action and measures focused on farm modernization. Otherwise the policy action can lead to the weak effects and inefficient use of public money. The paper is composed of four essential chapter. First chapters shows the evolution of historical features of the modernization. Next, the author presents theoretical aims, phases and ways of modernization processes. Third chapter is related to the modernization in the context of multi-dimension character of the economic processes. Finally modernization is reduced to the micro level, i.e. farm or firm level.